Keteraturan Aktifitas Senam Prenatal Yoga Terhadap Kenyamanan Ibu Hamil Trimester III - Sari, Atika Kurnia; Sari, Ekta Puspita; Mareza, Dianti (MIDWIFERY JOURNAL, 2025)
Background: During pregnancy, many pregnant women experience physiological changes during pregnancy that often cause discomfort or stress. One of the complaints or discomfort that pregnant women often experience is pain in the lumbopelvic area, back pain, and often BAK. Prenatal yoga plays a role in increasing the comfort of pregnant women, reducing pain, reducing anxiety and depression and improving pregnancy outcomes (Kartini, 2018).Purpose :  This study is to find out whether there is a relationship between the regularity of yoga prenatal gymnastics and the comfort of pregnant women in the third trimester.Methods : The type of research conducted on the relationship between the regularity of prenatal yoga gymnastics activities and the comfort of pregnant women in the third trimester at PMB Mery Handayani A.Md.Keb., SKM is a quantitative study.The samples in this study were selected using the total sampling method.Resullts: The research was of the study obtained from the bivariate analysis who experienced comfort after doing prenatal yoga exercises were 24 respondents and those who regularly did gymnastics amounted to 24 respondents. The results of the bivariate test with the results of the Chi-Square statistical test show that the count = 5.625 compared to the table = 3.841, then Ha is accepted. 2 2Conclusion :  Based on the results of the research, it can be concluded that ho is rejected and ha is accepted. This means that there is a relationship between the regularity of prenatal yoga gymnastics activities and the comfort of pregnant women in the third trimester at PMB Mery Handayani, A.Md.Keb., SKM in Gunung Labuhan Village, Blambangan Pagar District, North lampung Regency in 2025.Keyword : Prenatal yoga regularity, comfort of pregnant womenLatar Belakang : Pada masa kehamilan banyak ibu hamil yang mengalami Perubahan perubahan fisiologis pada masa kehamilan seringkali menimbulkan ketidaknyamanan ataupun stress. Salah satu keluhan atau ketidaknyamanan yang sering dialami ibu hamil adalah nyeri pada area lumbopelvic, nyeri punggung, dan sering BAK. Prenatal yoga berperan dalam meningkatkan kenyamanan ibu hamil, menurunkan nyeri, menurunkan kecemasan dan depresi serta meningkatkan outcomes kehamilan (Kartini, 2018).Tujuan : Penelitian ini untuk mengetahui apakah ada hubungan keteraturan senam prenatal yoga terhadap kenyamanan ibu hamil trimester III.Metode : Jenis penelitian yang dilakukan pada penelitian hubungan keteraturan aktifitas senam prenatal yoga terhadap kenyamanan ibu hamil trimester III di PMB Mery Handayani A.Md.Keb.,SKM adalah penelitian kuantitatif,.Sampel dalam penelitian ini dipilih nmenggunakan motode total sampling.Hasil : dari analisis bivariat yang mengalamali kenyamanan setelah melakukan senam prenatal yoga adalah 24 responden dan yang teratur melakukan senam berjumlah 24 responden. Hasil uji bivariat dengan hasil uji statistik Chi-Square menunjukan bahwa 2 hitung = 5,625 dibandikan dengan 2 tabel = 3,841 maka Ha diterima.Kesimpulan : Berdasarkan hasil penelitian, dapat diambil Kesimpulan bahwa ho ditolak dan ha diterima. Hal ini berarti ada hubungan antara keteraturan aktifitas senam prenatal yoga terhadap kenyamanan ibu hamil trimester III di PMB Mery Handayani A.Md.Keb.,SKM di Desa Gunung Labuhan Kecamatan Blambangan Pagar Kabupaten Lampung Utara Tahun 2025.Kata Kunci : Keteraturan Prenatal Yoga, Kenyamanan Ibu Hamil